KEPEMIMPINAN KIAI DALAM PEMBINAAN KARAKTER SANTRI PONDOK PESANTREN AGROPOLITAN NURUL MA’ARIF SUNGAI TEBELIAN KABUPATEN SINTANG - Latif, Abdul; Aunurrahman, Aunurrahman; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Islamic boarding schools are a benchmark in character building, therefore, all administrators, religious teachers and scholars to always be consistent and consistent in character building for every santri. The development of santri characters with educating systems and rules so that in the future santris will grow well too. The focus and purpose of this research was to describe Kiai's Leadership in the Development of Santri Characters, Santri activities in fostering the character of santri, and monitoring activities in fostering the character of santri. This study used a qualitative approach with descriptive research. Data collection techniques used include: In-depth interviews, observation and documentation. The results of this study were Kiai's leadership in the development of santri character of Kiai as a Motivator, namely Kiai often provides motivation so that santri can be more enthusiastic in positive things or good things. Kiai as an innovator, Kiai has made a renewal or breakthrough in an organization. Innovation is a movement that can provide a different atmosphere . Kiai as a facilitator, Kiai has provided facilities in the form of facilities and infrastructure to support activities in the pesantren. Kiai as mobilisator who moved in giving direction to subordinates, namely to ustadz-ustadzah.   Keywords:  Development of Santri Character, Kiai, Leadership.